Association between atopy and allergic contact dermatitis in Dr. Sardjito General Hospital Yogyakarta - Hardyanto Soebono, Fitria Retno Danarti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Association between atopy and development of allergic contact dermatitis (ACD) remains controversial. T cell disfunctions in a patient with atopy complicate the process of nickel sensitization. On the other, the decrease of the skin barrier function and overexpression of Langerhans cells in the patient facilitate the sensitization.Â  This study aimed to evaluate the association between atopy and incidence of nickel ACD. A case-control study was carried out in Allergic and Immunology Sub Department of Dermato-Venereology Policlinic, Dr. Sardjito General Hospital, Yogyakarta, involving 54 nickel ACD patients as case group and 74 healthy subjects as control group. All subjects underwent prick test allergens i.e. house dust, dust mite, cockroach, mixed fungi, nuts and egg white. The skin reaction was considered as a positive result if a wheal diameter of at least 3 mm larger than the negative control or a minimum of half of the positive control. The relationship between atopy and the nickel ACD incidence was analyzed using Chi-Square test with confidence interval (CI) of 95%. A significant association between atopy and the nickel ACD incidence was observed in this study. Subjects with atopy toÂ  â¥1 allergen had risk of nickel ACD 3.74 higher than subjects without atopy (odds ratio/OR=3.74; 95%CI = 1.64-8.53).Â  Furtheremore, subjects with atopy toÂ  â¥2 allergens had risk of nickel ACD 3.74 higher than subjects without atopy (OR=2.08; 95%CI = 1.01-4.29). In conclusion, atopy is a risk factor of nickel ACD. Key words: atopy - allergic contact dermatitis - nickel allergy â prick test â allergen